2021
DOI: 10.1016/j.numecd.2021.02.032
|View full text |Cite
|
Sign up to set email alerts
|

Association of the new visceral adiposity index with coronary artery calcification and arterial stiffness in Korean population

Abstract: Background and aims: The new visceral adiposity index (NVAI) is an indirect marker of visceral adipose tissue recently developed using a Korean population. Here we examined the association of NVAI with coronary artery calcification and arterial stiffness in asymptomatic Korean patients. Methods and results: We analyzed data from 60,938 asymptomatic Korean adults. Odds ratios and 95% confidence intervals (CIs) for coronary artery calcification score (CACS) > 100 and brachial eankle pulse wave velocity (baPWV) !… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…A positive relationship was noted between it and atherosclerotic cardiovascular disease risk [24]. Recently, a Korean study also found that the NVAI had the highest predictive value for coronary atherosclerosis and arterial stiffness among five obesity indices [25]. This study introduced a new perspective by extending the research on the correlation between the NVAI and clinical diseases from the cardiovascular field to the renal disease field.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…A positive relationship was noted between it and atherosclerotic cardiovascular disease risk [24]. Recently, a Korean study also found that the NVAI had the highest predictive value for coronary atherosclerosis and arterial stiffness among five obesity indices [25]. This study introduced a new perspective by extending the research on the correlation between the NVAI and clinical diseases from the cardiovascular field to the renal disease field.…”
Section: Discussionmentioning
confidence: 82%
“…Therefore, alternative parameters have been developed, including the visceral adiposity index (VAI) [14], Chinese VAI (CVAI) [15], lipid accumulation product (LAP) [16], a body shape index (ABSI) [17], and metabolic score for visceral fat (METS-VF) [18], which have been shown to be related to CKD [19][20][21][22][23]. Recently, it was documented that a new VAI (NVAI) had a higher predictive value for cardiovascular diseases than other obesity indicators in the Korean population [24,25]. However, research exploring any association between the NVAI and SRD is still absent.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, VAI and LAP indices were significantly higher in CAS patients than in controls. Son et al [ 26 ] assessed the relationship between the dynamic change of VAI and the risk of carotid plaque in 23522 Chinese participants. They calculated VAI at baseline and follow-up and found a significant positive correlation between VAI and carotid plaque risk (HR, 1.53; 95% CI, 1.48-1.59 [P 0.001]) in a nonlinear dose-response pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that VAT is associated with diabetes, hyperuricemia, metabolic syndrome, hypertension, atherosclerosis, and vascular calcification. [13][14][15][16][17][18] However, to our knowledge, the association between VAI and HF has not been studied.…”
Section: Introductionmentioning
confidence: 99%